Formation of residual stresses during discontinuous friction treatment - Hurey I.; Gurey V.; Bartoszuk M.; Hurey T. (Журнал інженерних наук)
The tool with grooves on its working surface is used to improve the properties of the strengthened layer. This allows us to reduce the structure’s grain size and increase the thickness of the layer and its hardness. Mineral oil and mineral oil with active additives containing polymers are used as a technological medium during friction treatment. It is shown that the technological medium used during the friction treatment affects the nature of the residual stresses’ distribution. Thus, when using mineral oil with active additives containing polymers, residual compressive stresses are more significant in magnitude and depth than when treating mineral oil. The nature of the residual stresses diagram depends on the treated surface’ shape. After friction treatment of cylindrical surfaces, the highest compressive stresses near the treated surface decreases with depth. And after friction treatment of flat surfaces near the treated surface, the compressive stresses are small. They increase with depth, pass through the maximum, and then decrease to the original values. The technological medium used during friction treatment affects residual stresses in the grains and in the crystal lattice.